2019
DOI: 10.1080/17512786.2019.1682942
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Commercial Influences: How Lifestyle Journalists Experience Pressure from Advertising and Public Relations

Abstract: The growth of advertising and PR industries in recent years, combined with the economic downturn in many news organizations has led to renewed debates about the influence of commercial pressures on journalistic work. While the relationship has frequently been studied in relation to hard news journalism, less attention has been paid to other beats, especially those which have always had a closer relationship with commercial interests. Focusing on the field of lifestyle journalism, this article presents the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…In this complex process of adaptation and reinvention, a renewed journalistic identity is emerging (Vos and Ferrucci, 2018) as are new forms of collaborative journalism with other professionals (Gans, 2018), together with more attention to the psychological framework (McIntyre and Gyldensted, 2018). Also evident is that more attention is being paid to human-machine relations in news writing (Lewis et al, 2019), as well as to journalistic friction with advertising and public relations professionals (Hanusch et al, 2020). Additionally, greater concern is shown for professional autonomy and professional status (Picard, 2005(Picard, , 2012.…”
Section: The Shadow Of Old and New Debatesmentioning
confidence: 99%
“…In this complex process of adaptation and reinvention, a renewed journalistic identity is emerging (Vos and Ferrucci, 2018) as are new forms of collaborative journalism with other professionals (Gans, 2018), together with more attention to the psychological framework (McIntyre and Gyldensted, 2018). Also evident is that more attention is being paid to human-machine relations in news writing (Lewis et al, 2019), as well as to journalistic friction with advertising and public relations professionals (Hanusch et al, 2020). Additionally, greater concern is shown for professional autonomy and professional status (Picard, 2005(Picard, , 2012.…”
Section: The Shadow Of Old and New Debatesmentioning
confidence: 99%
“…Several studies have showed how this framework is slowly being replaced by a culture of "collaboration, adaptation and business thinking", where working with other parts of the news medium is considered necessary by editors and business managers to ensure commercial sustainability (Cornia et al 2018;Westlund et al 2021). Many recent developments like native advertising, cross-functional product development, and entrepreneurial journalism have instigated the further blurring of these lines, creating internal tensions between commercial and editorial departments (Coddington 2015;De Smet and Vanormelingen 2011;Hanusch et al 2020;Artemas et al 2018). Merging these two sides is still a fairly new development, and yet some consider it vital for survival in a digital age (Laursen 2018;Newman 2019;Picard 2015;Vos and Singer 2016).…”
Section: Stakeholder Thinking At News Mediamentioning
confidence: 99%
“…There seems to be a strong innovation-oriented discourse among journalists that might influence their role perceptions, but when studying the interpretative repertoires of journalism students, they still seem to hold on to traditional views of journalistic roles (Singer and Broersma 2020). In the meantime, advertisers, ad departments, and media executives have increased the pressure for news media to create an advertiser-friendly environment (Artemas et al 2018;Baerug and Harro-Loit 2012;De Smet and Vanormelingen 2011;Hanusch et al 2020;An and Bergen 2007). Advertisers are moving from the side-line (banner ads) to a more embedded role with native advertising and online advertising that matches the form and function of editorial content (Wojdynski 2016).…”
Section: Journalists' Role Perceptionsmentioning
confidence: 99%
“…Nevertheless, the activities and innovations implemented by the news start-ups in the present study could be regarded as a pioneering practice that can make Chinese entrepreneurial journalism an exemplar for the global news industry. For entrepreneur journalists in Europe and America whose main sources of income are still advertisements and PR releases (Obermaier et al, 2018; Pedroni, 2015; Hanusch et al, 2020), this integrated model could be a new solution to the growing threats to editorial autonomy. Furthermore, it could be regarded as a pioneering practice that entrepreneurial journalism made to mitigate the longstanding conflicts between professionalism and commercialism that journalism has faced since the day it was born.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%